Answer: ![5.6^{3}+0.6^{2}+2.^{1}+4.6^{0}](https://tex.z-dn.net/?f=5.6%5E%7B3%7D%2B0.6%5E%7B2%7D%2B2.%5E%7B1%7D%2B4.6%5E%7B0%7D)
which will be 1096 in base 10
Step-by-step explanation:
in expanded form to base 10 will be :
![5.6^{3}+0.6^{2}+2.^{1}+4.6^{0}](https://tex.z-dn.net/?f=5.6%5E%7B3%7D%2B0.6%5E%7B2%7D%2B2.%5E%7B1%7D%2B4.6%5E%7B0%7D)
which will be
![5(216)+0(36)+2(6)+4(1)](https://tex.z-dn.net/?f=5%28216%29%2B0%2836%29%2B2%286%29%2B4%281%29)
⇒1080+0+12+4
= 1096
Answer:
What was this for ?
Step-by-step explanation:
Answer:
<h2><u><em>
n = 8</em></u></h2>
Step-by-step explanation:
2n + 1.6 = 17.6 what is the value of n?
2n + 1.6 = 17.6
2n = 17.6 - 1.6
2n = 16
n = 16 : 2
n = 8
-----------------
check
2n + 1.6 = 17.6
2*8+1.6=17.6
16+1.6=17.6
17.6=17.6
the answer is good
A) y = 2x – 7 and f(x) = 7 – 2xIncorrect. These equations look similar but are not the same. The first has a slope of 2 and a y-intercept of −7. The second function has a slope of −2 and a y-intercept of 7. It slopes in the opposite direction. They do not produce the same graph, so they are not the same function. The correct answer is f(x) = 3x2 + 5 and y = 3x2 + 5. B) 3x = y – 2 and f(x) = 3x – 2Incorrect. These equations represent two different functions. If you rewrite the first equation in terms of y, you’ll find the equation of the function is y = 3x + 2. The correct answer is f(x) = 3x2 + 5 and y = 3x2 + 5. C) f(x) = 3x2 + 5 and y = 3x2 + 5Correct. The expressions that follow f(x) = and y = are the same, so these are two different ways to write the same function: f(x) = 3x2 + 5 and y = 3x2 + 5. D) None of the aboveIncorrect. Look at the expressions that follow f(x) = and y =. If the expressions are the same, then the equations represent the same exact function. The correct answer is f(x) = 3x2 + 5 and y = 3x2 + 5.
Answer:
Step-by-step explanation:
f(x)= x^2 - 6x + 8
a of s= 6/2 = 3
(3)^2 - 6(3) + 8
9 - 18 + 8
-9 + 8 = -1
(3, -1)
answer is B